Community-based household assessment of human papillomavirus (HPV) vaccination coverage and acceptability – HPV vaccine demonstration program, Cambodia – 2017. Issue 9 (21st February 2019) - Garon, Julie; Wuddhika, In Vong; Sreenivasan, Nandini; Wannemuehler, Kathleen; Vutthikol, Yong; Chhorvann, Chhea; Loharikar, Anagha
Abstract: Background: In 2017, the Cambodia Ministry of Health introduced human papillomavirus (HPV) vaccine through primarily school-based vaccination targeting 9-year-old girls. Vaccination with a two-dose series of HPV vaccine took place in six districts in two provinces as a demonstration program, to better understand HPV vaccine delivery in Cambodia. Methods: We conducted a community-based coverage survey using a one-stage sampling design to evaluate dose-specific vaccination coverage among eligible girls (those born in 2007 and residents in the areas targeted by the campaign). The household-level survey also assessed factors associated with vaccine acceptability and communication strategies. Trained data collectors interviewed caregivers and girls using a standard questionnaire; vaccination cards and health facility records were reviewed. Results: Of the 7594 households visited in the two provinces, 315 girls were enrolled in the survey (188 in Siem Reap; 127 in Svay Rieng). Documented two-dose HPV vaccination coverage was 84% (95% confidence interval [CI]: 78–88%) overall [85% (95% CI: 78–90%) in Siem Reap; 82% (95% CI: 73–88%) in Svay Rieng.] Almost all girls (>99%) were reported to be enrolled in school and over 90% of respondents reported receipt of vaccine in school. Knowledge of HPV infection and associated diseases was poor among caregivers and girls; however, 58% of caregivers reported "protection from cervical cancer" as the primary reason for the girl receiving vaccine. No serious adverse events after immunization were reported. Conclusions: The HPV vaccine demonstration program in Cambodia achieved high two-dose coverage among eligible girls in both provinces targeted for vaccination in 2017, through primarily school-based vaccination. High school enrollment and strong microplanning and coordination were seen throughout the campaign. Cambodia will use lessons learned from this demonstration program to prepare for national introduction of HPV vaccine.